Developing a systematic search strategy related to people with disability: A brief report testing the utility of proposed disability search terms in a search about opioid use. Issue 2 (April 2019) - Ioerger, Michael; Flanders, Reed M.; Goss, Katherine D.; Turk, Margaret A.
Abstract: Background: The varied use of the term "disability" in the scientific literature makes it challenging to conduct systematic reviews of health issues among people with disability. Utilizing general disability search terms has been suggested as an efficient way to ensure a broad capture of the literature related to disability. Objectives: This study evaluates the utility of general disability terms versus condition-specific terms, in the context of systematically searching for articles related to disability and other conditions or issues, in this case, opioid use. Methods: Systematic searches were conducted using three databases. An initial search of articles mentioning opioids and disability was conducted employing the general search terms recommended by Walsh et al. 1 The results were then compared to 16 condition-specific searches. The proportion of unique articles from each condition-specific search that overlapped with the general search was assessed. Results: There was very little overlap between the articles captured using condition-specific search terms and the articles captured utilizing the general search terms. The highest amount of overlap was for spinal muscular atrophy at 33.3%, with the overall median proportion of overlap being 13.4% (mean = 15.7%; SD = 11.7%). Conclusions: With a systematic search for articles about disability associated with opioid use as an example, condition-specific search terms capture a large proportion of articles not identified using general disability search terms. Disability researchers should be aware of pitfalls using general terminology and the importance of using disability-specific search terms.